PERAN MANGROVE (Avicennia sp.) TERHADAP PERTUMBUHAN BANDENG (Channos channos) DI DESA KEJAWAN PUTIH, KECAMATAN SUKOLILO, SURABAYA TIMUR - Alia Damayanti (Purifikasi, 2006)
Mangrove ecosystem is very sensitive to environmental changes. As feeding, nursery and spawning grounds and ultrafiltrator, mangrove ecosystem supports the fishery activities. Milkfish (Channos-channos) is a fish species, which is widely cultured in Indonesia. Three locations of milkfish aquaculture with different levels of mangrove density in Kejawan Putih was chosen for determining its influence to milkfish growth and productivity. The values of pH, dissolved oxygen, BOD, and total dissolved solids of the fishpond water and the water source were analysed twice per month for 3 consecutive months. Sizes of the harvested milkfish were measured according to its length, width, and weight. Results of this research showed that aquaculture with ± 10% of mangroves provided 80 % of milkfish life expectancy, with average length of 32 cm, and average weight of 300 gr. Aquaculture with no mangrove gave less than 60% milkfish life expectancy, with average length of 29,5 cm, and average weight of 150 gr.